Dynamics of osteopontin levels and correlation with parasitemia in acute malaria in Uganda and Sweden - Mortazavi, Susanne E; Lugaajju, Allan; Danielsson, Lena; Wu, Bingyan; Norrgren, Hans; Persson, Kristina E. M (BMC Infectious Diseases, 2024)
Background Malaria remains a signifcant public health concern, especially for the deadliest parasite, Plasmodium falciparum. During acute malaria, various cytokines, including osteopontin (OPN), regulate the immune response. OPN has been shown to be protective against malaria in mice. Nonetheless, its precise function and potential ability to control parasites during acute malaria in humans remain poorly understood. Results Blood samples were collected from Swedish adults with imported malaria, Ugandan children and adults with symptomatic malaria (including follow-up after 42 days), Ugandans with non-malarial fever and healthy individuals from both Uganda and Sweden. Parasitemia was determined by microscopy. Malaria-negative samples were verifed by LAMP. OPN and interferon-γ (IFN- γ) levels were measured using ELISA. In children, OPN levels were signifcantly higher during acute infection compared to levels after 42 days, whereas Ugandan adults showed no diference. Swedish adults with imported malaria had elevated OPN levels compared to both Swedish controls and Ugandan adults with malaria. Parasitemia was signifcantly correlated with both OPN and IFN-γ levels across the entire cohort. While a signifcant correlation between OPN and IFN-γ was evident overall, it remained statistically signifcant only in Ugandan adults when analyzed by subgroups. This suggests that OPN is not just a general marker of infammation but may be regulated diferently during the development of malaria immunity. Conclusions In acute malaria, elevated OPN levels showed a stronger correlation with lack of immunity than age. These fndings underscore the potential importance of OPN in malaria, particularly in non-immune individuals. Keywords Malaria, Osteopontin, Parasitemia, Imported malaria, Immunity, ELISA, LAMP, IFN- γ